2023
DOI: 10.5009/gnl220522
|View full text |Cite
|
Sign up to set email alerts
|

Comments on Comparison of Sorafenib versus Hepatic Arterial Infusion Chemotherapy-Based Treatment for Advanced Hepatocellular Carcinoma with Portal Vein Tumor Thrombosis: Reply

Abstract: We appreciate the letter from Deng and colleagues regarding our study. They raised several questions related to the treatment of hepatocellular carcinoma with sorafenib or hepatic arterial infusion chemotherapy (HAIC). 1 First, they were curious about combination therapies. As we described in the combination and second-line therapy section, patients in the HAIC group more frequently (68%) received combination such as transarterial chemolipiodolization (15.3%), radiotherapy (26.3%), or both therapies (23.7%) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Previously, sorafenib was the sole recommended systemic drug for liver cancer patients with portal vein tumor thrombosis (PVTT), but monotherapy with sorafenib did not yield satisfactory outcomes [10][11]. A recent largescale retrospective study conducted across multiple centers in Japan demonstrated no significant difference in overall survival (OS) and progression-free survival (PFS) between hepatic arterial infusion chemotherapy (HAIC) and sorafenib treatment in patients without macrovascular invasion (MVI).…”
Section: General Informationmentioning
confidence: 99%
“…Previously, sorafenib was the sole recommended systemic drug for liver cancer patients with portal vein tumor thrombosis (PVTT), but monotherapy with sorafenib did not yield satisfactory outcomes [10][11]. A recent largescale retrospective study conducted across multiple centers in Japan demonstrated no significant difference in overall survival (OS) and progression-free survival (PFS) between hepatic arterial infusion chemotherapy (HAIC) and sorafenib treatment in patients without macrovascular invasion (MVI).…”
Section: General Informationmentioning
confidence: 99%